Green synthesis of europium oxide nanoparticles via Vitex trifolia: Biomedical applications in infection control and cancer therapy - Tiyah Jimmy Chheda; Rajakumar Govindasamy; Suganya Panneer Selvam; Dhivya Viswanathan (Pharmacological Research - Modern Chinese Medicine, 2025)
Objective: This study aims to synthesize europium oxide nanoparticles (Eu₂O₃ NPs) using Vitex trifolia leaf extract through a green synthesis approach and evaluate their antibacterial and anticancer properties for potential biomedical applications. Methodology: Eu₂O₃ NPs were synthesized from Vitex trifolia leaf extract using 0.4 M europium nitrate, 1 M sodium borohydride, and ammonia, confirmed by a color change. The nanoparticles were characterized using FTIR, XRD, and SEM, while their antibacterial activity was assessed against Pseudomonas aeruginosa, Streptococcus mutans, Enterococcus sp., and Klebsiella sp. via the agar well diffusion method. Cytotoxicity assays on A549 cancer cells evaluated anticancer potential, with the IC50 value determined through dose-response analysis. Results: XRD and SEM analysis confirmed that the synthesized Eu₂O₃ NPs had an average size of 82 nm, while FTIR spectra revealed the presence of phytochemicals involved in nanoparticle stabilization. Antibacterial assays using the agar well diffusion method demonstrated significant activity, with Enterococcus sp. showing the highest sensitivity, exhibiting inhibition zones of 19 ± 0.49 mm, 15 ± 0.35 mm, 17 ± 0.45 mm, and 18 ± 0.53 mm at varying concentrations. Cytotoxicity assays on A549 cancer cells showed a dose-dependent reduction in cell viability. The IC50 value for anticancer activity was approximately 100 µg/mL, confirming effective cancer cell inhibition. Conclusion: The biogenic synthesis of europium oxide (Eu₂O₃) nanoparticles utilizing extract from Vitex trifolia presents an environmentally friendly and sustainable method for nanoparticle production. These nanoparticles exhibited significant antibacterial properties and notable anticancer potential, positioning them as promising candidates for biomedical applications, particularly in the realms of antimicrobial therapy and cancer treatment.